INOVASI KEBIJAKAN PEMERINTAH DESA DALAM PENGEMBANGAN DESA WISATA KERTOSARI KECAMATAN PURWOSARI KABUPATEN PASURUAN - Yunita, Ita; Lutfi, Mochammad; Fauzi, M. Asif Nur (Jurnal Inovasi Daerah, 2023)
This research is motivated by the development of tourism in the village in an effort to optimize the village's potential to be utilized as a tourist village destination. The role of the community in this development is a form of shared commitment. However, in this development effort literacy related to tourism awareness is still low and must be overcome so that community awareness of tourism villages can be realized. This study uses field research (field research) with a qualitative approach. Data collection techniques are carried out through observation, interviews, and documentation. Data analysis was performed using data collection techniques, data reduction, data presentation, and drawing conclusions. Based on the results of the research conducted, the development of the Kertosari tourism village is a tourist destination that combines aspects of recreation and education by optimizing the potential that the village has. In the scope of increasing the community's economy, the presence of tourist villages has a very positive impact, especially on the sale of agricultural products. Suggestions that can be conveyed are the importance of the role of tourism awareness groups (Pokdarwis) in increasing the existence of the Kertosari tourist village both in terms of the number of tourists and community economic empowerment through the use of social media as a means of digital tourism information. This shows that the role of Pokdarwis is not only as tourism manager but also as tourism marketing